A Study on The Relationship Between Corporate Culture and Accounting System in Improving Dust Blower Facility Management at Mahindra and Mahindra, Nagpur - Halwale, Payal Champatrao; Tekade, Atul (Journal of Neonatal Surgery, 2025)
Corporate culture significantly influences the operational effectiveness of accounting systems, particularly in specialized domains such as dust blower facility management. This study explores the intricate relationship between organizational culture and accounting frameworks in optimizing management practices at Mahindra and Mahindra, Nagpur. Emphasizing a cohesive corporate culture fosters transparency, accountability, and efficiency, thereby enhancing the decision-making capabilities of the accounting system. The research employs a mixed-methods approach, combining quantitative data analysis with qualitative insights, to examine how cultural elements such as employee engagement, leadership styles, and organizational values integrate with accounting practices to streamline facility operations. Key findings reveal that a robust alignment between corporate culture and accounting systems leads to improved cost control, reduced downtime, and enhanced resource utilization within the dust blower management facility. Furthermore, the study identifies critical barriers to this alignment, including communication gaps and resistance to change, proposing strategic interventions to address these challenges. Insights derived from the research contribute to the broader discourse on integrating cultural and accounting frameworks to achieve operational excellence. The findings offer actionable recommendations for practitioners and managers seeking to enhance their facility management capabilities through culturally aligned accounting practices, ensuring sustainable growth and improved efficiency.